Mobilities on the Margins Creative Processes of Place-Making - Thorsteinsson, Björn; Lund, Katrín Anna; Jóhannesson, Gunnar Thór; Jóhannesdóttir, Guðbjörg R. (Arctic Encounters, 2024)
This open access book examines places on the margins and the dynamics through which a marginal position of a place is created. Specifically, it explores how places, mostly in sparsely populated areas, often perceived as immobile and frozen in time, come into being and develop through interference of everyday mobilities and creative practices that cut across the spheres of culture and nature as usually defined. Through fieldwork and case studies from areas in Iceland, Finland, Greenland, and Scotland, the book's twelve chapters draw out the multiple relations through which places emerge, where people compose their lives as best they can with their surroundings. A special concern is to explore the links between travelling, landscape, and material culture and how places and margins are enacted through mobilities and creative practices of humans and other beings. The emphasis on mobility disturbs the perception of a place as a bounded entity and offers a useful and necessary understanding of places as mobile and fluid. Mobilities on the Margins is a novel and timely contribution to the exploration of human and more-than-human interactions in a world of increasingly fluid mobilities and insistent crises.